The Structure of Online Information Behind Social Crises - Cárdenas, Juan Pablo; Olivares, Gastón; Vidal, Gerardo; Urbina, Carolina; Fuentes, Miguel (Frontiers in Physics, 2021)
The adaptive nature of the social system allows it to overcome the challenges imposed by its environment as well as to overcome those internal pressures. This adaptive process is associated with an increase in complexity manifested in a greater diversity of its components, new forms of organization, among other transformations. However, these adaptations have a cost and need to be administered, otherwise, they can trigger social unrest and crisis processes. Currently, the adaptive process of social systems has been accelerated and magnified by the emergence of information technologies. In this work, we explore the close relationship between adaptation, complexity, and crisis, showing it expression in a digital social environment, although with some particularities. Specifically, we have observed expected behaviors, such as the polarization of society and negative sentiment of messages during times of crisis, however, our results show something interesting. Despite the loss of order in the social organization questioned by the crisis, we observe the emergence of new complex ephemeral structures of information which seem to be early-warnings signals of profound social transformations.